Demographic profile and level of resilience as correlates to coping strategies of parents of children with special needs: basis for parental adaptability program - Rances, Georgnen C. et.al. 4 0 16; 5 (2017)
ABSTRACT: This study was designed to measure the level of resilience of parents of children with special needs, their coping strategies and its significant relationship and difference when grouped according to their demographic profile through the use of Resilience Scale and Coping Strategies Inventory. The researchers used purposive sampling technique in selecting 100 respondents with the following criteria: a) the respondent could be either biological or foster parent, b) the parent should have at least one child with special needs regardless of child's age, gender and case, c) the respondent should be living together with the child, d) the parent should be at the one who are taking care of the child. Also, Descriptive and Inferential Statistical technique were used to analyse the gathered data. Furthermore, it was concluded that parents who have low level of resilience adopt negative coping strategies while parents who are in the moderate level of resilience employ fewer positive coping strategies. Hence, the researchers recommended a program that would help parents to adapt in stressful situations for them to be able to manage and deal with it through using positive coping strategies.
Undergraduate Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2